The Wadiah and Wakalah approach for missing person’s property / Nur Nadirah Akmar Mokhtar … [et al.] - Akmar Mokhtar, Nur Nadirah; Sulaiman, Muhammad Azwan; Zainol, Nurul Nadiah; Wan Yusoff, Wan Zahari (UiTM Press, 2023)
Missing Person’s property issues in Malaysia have become increasingly complicated since the MH370 tragedy. When a person is missing and cannot be traced, the Islamic law of Al-Mafqud dictates that their property is managed in a specific way. By 2021, the estimated value of the missing person's property was estimated to be in the billions of ringgit, indicating the need for an efficient property management system. To ensure a smooth operation, there is a need for effective management and efficient estate planning towards the missing person’s property. Document analysis was employed to allow for a comprehensive examination of the data. This paper presents the results of secondary data collected from various sources such as policy documents, legislative acts, research papers, articles, and newspapers about previous cases. In general, it is proposed that the principles of Wadiah and Wakalah in Islam are suitable approaches for solving the issue of missing person’s property in Malaysia. Wadiah is a principle where a Trustee can manage a property, and any profit from the property can be shared. Wakalah is a contract where a person authorizes another to do a particular well-defined legal action on their behalf. Thus, Wadiah and Wakalah could be potential solutions to the issue of missing person's property in Malaysia.